Insert formulation and characterization of empty fruit bunch compost formulation as soilless growing media for ornamentals - Baharudin, Sarah; Abdullah, Thohirah L.; A. Bakar, Rosenani (AIDIC Servizi S.r.l., 2023)
One of the leading environmental effects of many systems in horticulture, such as soilless culture, is the generation of organic plant residues and substrate wastes. Nowadays, there is a higher demand for ecologically friendly and lower-cost substrates. There is high interest in assessing compost from agro-wastes that can be used as growing media. This study aimed to test for phytotoxicity effect and evaluate the chemical and physical properties of substrates formulated from oil palm empty fruit bunch (EFB) compost as the main component and EFB biochar, rice husk (RH) biochar, vermiculite, sewage sludge and cocopeat as additives. The components were formulated in different ratios forming 18 formulations, including controls. Experiments were conducted in stages. First was a germination assay phytotoxicity test using Solanum lycopersicum (Tomato) seeds, and nine formulations were shortlisted (highest germination rate and best root growth within incubation days). The selected formulations were then analyzed for physical and chemical characteristics. The final four formulations were selected for pot trial; 10VRM (10 % vermiculite + 90 % EFB compost), 10 EBC (10 % EFB biochar + 90 % EFB compost), 10SWS (10 % sewage sludge + 90 % EFB compost) and 10 RHB (10 % rice husk biochar + 90 % EFB compost). These four formulations are potentially used as growing media because they show a high germination rate (>90 %), low phytotoxicity (<5 %), pH near neutral and high amount of nutrient content. In the following study, the potting media that depicted the best growth and flowering qualities is formulation 10RHB for growing Molineria latifolia var. megacarpa. It produced the tallest plant height (34.99 cm), the most number of flowers (5.93 nos) and the highest number of leaves (5.3 nos), as well as the earliest day to flowering amongst treatments (31.4 d). Rhodomyrtus tomentosa planted in 10 EBC showed the best growth compared to the other three formulations tested, with the tallest plant height (63.35 cm), the most number of flowers (23.93 nos), the highest number of leaves (308.9 nos) and earliest day to flowering amongst treatments (70.6 d). The two best recommendations are 10RHB (90 % EFB Compost + 10 % rice-husk biochar), and 10 EBC (90 % EFB Compost + 10 % EFB biochar) to grow both ornamental landscape plants. EFB compost-based with biochar as additives are potential soilless media formulations that could be utilized as potting media compared to other soil-only based mixtures in the current ornamental industry.